Rekonstruksi Pendidikan untuk Dusun Kopeng melalui Edukasi dan Pemberdayaan Masyarakat - Yudianto, M. Riko; Oktavia, Viola Dwi; Hasna, Neha Amelia; Rahmawati, Rani Dwi; Anwar, Hisyam Faizul; Azhara, Rafito Anwar; Hari, Ellia Pingky Dini; Hadin, Achmad Reihan; Purnama, M. Dopris; Ratnawati, Dila Saputri; Asroni, Asroni (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
This outreach program aims to enhance the understanding of Dusun Kopeng residents regarding the prevention and control of Foot-and-Mouth Disease (FMD) in livestock. FMD is a contagious disease that can cause significant economic losses for farmers, especially in areas like Dusun Kopeng, where the majority of the community depends on beef cattle farming for their livelihoods. Therefore, the community service team from Universitas Muhammadiyah Yogyakarta (UMY) conducted a socialization program to empower the community with knowledge about FMD. The objective of this program is to improve farmers’ understanding of FMD prevention and management. The methods employed in this community service initiative included interviews, observations, and direct community outreach. The results of the program indicate that the outreach activities successfully raised community awareness and capacity in preventing and managing FMD through early detection, proper barn sanitation, and timely reporting of symptoms to veterinary officers. This program is expected to support the sustainability of livestock farming and improve the well-being of the Dusun Kopeng community. The FMD outreach program in Dusun Kopeng has effectively equipped local farmers with essential knowledge for preventing and controlling a disease that poses a serious threat to their livestock.